PESQUISA DE DNA DE PLASMODIUM EM AMOSTRAS DE FÍGADO DE SÍMIOS MORTOS VITÓRIA 2020 - Furieri, Cintia (2020)
Malaria is a major global public health problem. Although notorious for the distribution of cases in the Amazon region, it is also known to be endemic in the dense forests of southeastern Brazil. The infection is called residual malaria from Atlantic Fore